Social media and crisis communication - Austin, Lucinda L.; Jin, Yan (Sociologist)
"The second edition of this vital text provides theory, research, and application to orient readers to the latest thinking about social media usage in crisis communication. Specific crisis arenas such as health, corporate, nonprofit, religious, political, and disaster are examined in depth and social media platforms and newer technology types are discussed. Social Media and Crisis Communication provides a fresh look at the role of visual communication in social media and a more global review of social media and crisis communication literature. With an enhanced focus on ethics section, a short communication overview piece, and case studies for each Area of Application, Social Media and Crisis Communication is practical for use in a variety of learning settings. A must-read for scholars, advanced students, and practitioners who wish to stay on the leading-edge of research, this book will appeal to those in public relations, strategic communications, corporate communications, government and NGO communications, and emergency and disaster response"--Provided by publisher.